SYSTEMATIC LITERATURE REVIEW: EMPOWER LEADERSHIP AND ROLE INTRINSIC MOTIVATION AS A MEDIATION VARIABLE IN IMPROVING EMPLOYEE PERFORMANCE - Yuliza Yuliza; Hendra Musa (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2023)
ABSTRACTThis study aims to determine Empower Leadership and the Role of Intrinsic Motivation as a Mediation Variable in Improving Employee Performance. The method used in this research is a systematic literature review (SLR) of journal articles published in 2015-2021 with PICOC criteria. Based on the results of a literature analysis on 11 selected journals, each variable has a coverage percentage of 90.9% for Empower Leadership, 63.6% for Intrinsic Motivation, and 90.9% for employee performance variables. The Empower Leadership variable has a percentage of 90.9%, namely 10 journals out of 11 selected journals that discuss Empower Leadership. Empower Leadership in some of the literature reviewed was found to be able to influence employee motivation and performance.ABSTRAKPenelitian ini bertujuan untuk mengetahui Empower Leadership Dan Peran Intrinsic Motivation Sebagai Variabel Mediasi Dalam Meningkatkan Employee Performance. Metode yang digunakan dalam penelitian ini adalah systematic literature review (SLR) artikel jurnal yang diterbitkan tahun 2015-2021 dengan kriteria PICOC. Berdasarkan hasil analisis literatur pada jurnal terpilih sebanyak 11 jurnal, masing-masing variabel memiliki persentase cakupan sebesar 90,9 % untuk Empower Leadership, 63,6% untuk Motivasi Intrinsik, dan 90,9 % untuk variabel kinerja karyawan.  Variabel Empower Leadership mempunyai persentase sebesar 90,9% yaitu 10 jurnal dari 11 jurnal terpilih yang membahas mengenai Empower Leadership. Empower Leadership dalam beberapa literatur yang dikaji ditemukan mampu memberikan pengaruh terhadap motivasi dan kinerja karyawan.